Lethality of SQL injection against current and future Internet-technologies - Pathan, Al-Sakib Khan; Diallo, Abdoulaye Kindy (Inderscience Publishers, Switzerland, 2014)
SQL Injection attack is often used as the underlying technology for hacking, which has made significant number of news headlines in the recent years. A vast majority of the readers do not have a clear idea how SQL Injection attack is used for hacking. In this article, we analyze this technology from necessary angles and discuss how this could be a significant potential threat for the future Web and Internet technologies.